Bank selection and customers' perception of banks in Malaysia - Ismail, Norhazlin; Selamat, Zarehan; Ong, Hway-Boon (The Philippine Review of Economics, 2004)
The process customers go through in choosing a bank has been studied for several decades using different approaches. Understanding the needs and analyzing how the customers select their banks are crucial steps towards the improvement of customer satisfaction. In this study, an attempt is made to identify the determinants of bank selection and customers' perception of banks in Malaysia.